2018
DOI: 10.1080/09593985.2018.1467520
|View full text |Cite
|
Sign up to set email alerts
|

Basic Body Awareness Therapy in patients suffering from fibromyalgia: A randomized clinical trial

Abstract: This study showed that BBAT might be an effective intervention in patients suffering from fibromyalgia in relation to pain, movement quality, and anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 36 publications
0
32
0
1
Order By: Relevance
“…By integrating the aching body into the self-trusting cooperation between body and self can be developed [25]. BBAT has in a recent randomised controlled study been shown to reduce pain in patients with fibromyalgia [28].…”
Section: Discussionmentioning
confidence: 99%
“…By integrating the aching body into the self-trusting cooperation between body and self can be developed [25]. BBAT has in a recent randomised controlled study been shown to reduce pain in patients with fibromyalgia [28].…”
Section: Discussionmentioning
confidence: 99%
“…In the Scandinavian countries, and there particularly within the frame of physical therapy and psychiatric care, body-awarenessbased interventions have been developed and widely implemented. One example is basic body awareness therapy (Bravo, Skjaerven, Espart, Sein-Echaluce, & Catalan-Matamoros, 2019): Changes in movement patterns and body-awareness-related treatment effects are assessed by trained physical therapists using a standardized semiqualitative observation scale (a method of second-person assessment), often in addition to detailed first-person, qualitative assessments.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown the relationship between body awareness and other clinical problems, such as irritable bowel syndrome, fibromyalgia and chronic pain, use of prostheses, and eating disorders 3 , 5 , 8 , 9 ) . Catalan-Matamoros et al have reported that basic awareness therapy is effective in improving some symptoms in outpatients with eating disorders.…”
Section: Discussionmentioning
confidence: 99%